Failure contraception in Indonesia: IDHS 2012 data analysis - Rahmatiqa, Chamy; Wilopo, Siswanto Agus; Purwasari, Shinta (International Journal Of Community Medicine And Public Health, 2019)
Background: Contraception prevalence rate (CPR) increased from the year 1991 is 50% to 62% in 2012 but Totak fertility rate (TFR) was little changed at data IDHS 2002-2003, 2007, and 2012 that is 2.6. Of IDHS 2007, the failure of contraception reflects the result in the unwanted pregnancies that can result in high maternal mortality and morbidity of the baby in the year 2012. The research aims to assess the failure of the contraceptive couples of childbearing age in Indonesia. Methods: Research was the observational study design with a cohort-retrospective. Researchers analyzed longitudinal data using calendar data IDHS 2012. The sample was 10.250 women of childbearing age ever married aged 15-49 years and the use of contraceptives. The analysis of contraceptive failure based on the predictor performed with the cox proportional hazard model by using curves Kaplan-Meier. Results: The most effective contraceptives found that the Implant (0.56) and the IUD (0.75) this was a modern contraceptive. The failure rate of the most high was neither disconnected (8.93) and periodic abstinence (7.32) this is the traditional contraception. The injectable and the pill was the choice of the majority of the respondents. The failure rate of the most high according to modern methods of contraception was injectables (35.67%), while the traditional method is neither disconnected (15.34%). Conclusions: The traditional method was the potential of failure compared to modern methods of contraception that may increase the unwanted pregnancy.